Explanatory Theories of Stock Returns in the Long Run after IPO - Literature Review - Martyna Żyła (Nauki o Finansach)
Negative returns of shares in the long run after initial public offerings have been confirmed on many markets, however the explanation for the cause of this phenomenon is ambiguous. Investigating underperformance is important because it allows for a better understanding of the role of the stock markets in the financial system. Such a market anomaly influences the behaviour of investors in the long run. Underperformance features in an extensive body of empirical literature and has been confirmed in most cases, yet it is inconclusive as to what affects such phenomenona on the markets. The purpose of this paper was to present the explanatory theories based on the behaviour of market participants and to summarise the explanatory variables of underperformance that stem from the theory.(original abstract)